Managing collaborative effort: how Simmelian ties advance public sector networks - Lemaire, Robin H.; Provan, Keith G. (2018)
The research reported here is a structural analysis of the significance of ties to network leaders in securing the essential effort necessary to whole, goal-directed network functioning. Drawing on the work of Chester Barnard, we focus on one of Barnard$1 (Bs three functions of the executive, securing essential effort and then examine the importance of certain network ties for securing effort in a goal-directed network. We specifically focus on Simmelian or mutual third-party ties to network leaders and the conditions under which those Simmelian ties are of greater significance for securing effort. Our study examines the Southern Alberta Child and Youth Network (SACYHN), a multisector publicly funded network that worked to facilitate interorganizational connections to improve child and youth health and well-being. Data were collected via an organizational questionnaire and elite interviews and were analyzed using Multiple Regression Quadratic Assignment Procedure (MRQAP). Implications are discussed for network management and leadership, for both theory and practice, focusing especially on the role of ties to network leaders in facilitating connections among member organizations working in different domains. - Reproduced. s
Keywords: Networks; Network analysis